Life at Age 100: An International Research Agenda for Centenarian Studies. Issue 3 (2nd July 2016) - Jopp, Daniela S.; Boerner, Kathrin; Ribeiro, Oscar; Rott, Christoph
ABSTRACT: Living a long life is desired by many individuals, and this dream is likely to become reality in more and more industrialized societies. During the past 3 decades, the number of very old individuals has increased significantly, creating a global demographic challenge with consequences at the individual, family, and societal levels. Yet, life in very old age is still poorly understood in terms of its unique characteristics and challenges. Besides specific content areas, very old age represents an understudied field of research. This lack of knowledge may be one reason that the very old also are an underserved population. This special issue introduces an international network of three centenarian studies that describe and compare the life circumstances and characteristics of centenarians across Germany, Portugal, and the United States. Our parallel studies comprehensively assess centenarians' physical, cognitive, social, and psychological functioning to create a knowledge base regarding their capacities and needs. A specific focus lies in the investigation of psychological aspects, social resources, and societal/cultural contexts, factors that may contribute to longevity and successful aging. Determining key characteristics of this very old population and investigating similarities and differences across countries is timely and urgent, both from an applied and a policy standpoint.